2014
DOI: 10.1016/j.fcr.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Inter-relationships of cotton plant height, canopy width, ground cover and plant nitrogen status indicators

Abstract: a b s t r a c tPetiole-NO 3 , leaf N and chlorophyll (SPAD) meter readings are good in-season indicators of the N status of the uppermost part of cotton (Gossypium hirsutum L.) plants. , particularly is widely used in the USA as an in-season plant N test that guides N fertilizer recommendations in cotton. However, these N status indicators do not take account of plant biomass, canopy width or percent cover. The objectives of this study were to assess the effect of N fertilizer rates on the commonly used indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…Plant height can be obtained from the crop surface model (CSM), which is created by using structure-from-motion techniques. Several studies have already used CSM to estimate plant height and biomass for various crops, including maize [1517], rice [18], barley [19, 20], cotton [21, 22], sugarcane [23], wheat [24] and sorghum [16, 25]. Previous studies have confirmed that combining spectral information and plant-height information can improve biomass estimates [1, 2629].…”
Section: Introductionmentioning
confidence: 99%
“…Plant height can be obtained from the crop surface model (CSM), which is created by using structure-from-motion techniques. Several studies have already used CSM to estimate plant height and biomass for various crops, including maize [1517], rice [18], barley [19, 20], cotton [21, 22], sugarcane [23], wheat [24] and sorghum [16, 25]. Previous studies have confirmed that combining spectral information and plant-height information can improve biomass estimates [1, 2629].…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient N fertilizer application causes premature senescence, while excessive application causes late ripening and increases environmental pollution. Recent studies have measured the impacts of N fertilization on cotton (Pettigrew and Adamczyk, 2006;Alitabar et al, 2012;Zhang et al, 2012;Muharam et al, 2014;Luo et al, 2018). Root growth is significantly affected by N fertilization, for example, Gaudin and Tian showed that low N levels enhanced root elongation (Tian et al, 2008;Gaudin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the emergence of global environmental issues, rising awareness of global warming and the increased cost of nitrogen have spurred an interest in the investigation of nitrogen fertilization. A number of studies over the past few decades have investigated the effects of nitrogen on cotton growth [12][13][14]. These studies focused on the effects of nitrogen application on cotton leaves or on lint yield.…”
Section: Introductionmentioning
confidence: 99%